2007
DOI: 10.1016/j.bbapap.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

An integrated analysis of the effects of Esculentin 1–21 on Saccharomyces cerevisiae

Abstract: The antimicrobial peptide esculentin 1-21 (Esc 1-21) is a shorter synthetic version of the 46-residue peptide occurring in the Rana esculenta skin secretion. Here we propose an integrated proteomic and transcriptomic approach to interpret the biological effects of this peptide on Saccharomyces cerevisiae. We further investigated the response to this peptide by correlating the results of the transcriptome and proteome analysis with phenotypic effects. The results show that S. cerevisiae adapts to Esc 1-21 using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Note that only a few studies on the effect(s) of antimicrobial peptides on the proteomes of microorganisms have been performed to date. Interestingly, proteomic and transcriptomic analysis of the yeast Saccharomyces cerevisiae, following exposure to a similar antimicrobial peptide [esculentin-1a(1-21)], had shown downregulation of enzymes of the lower glycolytic pathway as well as a decrease in actin level, resulting in dramatic changes in cell physiology [57]. It is worthy of remark that both fragments of esculentin peptide were found to affect the integrity of the microbial plasma membrane and the synthesis of the microbial cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…Note that only a few studies on the effect(s) of antimicrobial peptides on the proteomes of microorganisms have been performed to date. Interestingly, proteomic and transcriptomic analysis of the yeast Saccharomyces cerevisiae, following exposure to a similar antimicrobial peptide [esculentin-1a(1-21)], had shown downregulation of enzymes of the lower glycolytic pathway as well as a decrease in actin level, resulting in dramatic changes in cell physiology [57]. It is worthy of remark that both fragments of esculentin peptide were found to affect the integrity of the microbial plasma membrane and the synthesis of the microbial cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that esculentin-1a(1-21) NH 2 [Esc(1-21)] derived from the N-terminal region of the 46 residues frog skin AMP esculentin-1a (Gamberi et al 2007;Islas-Rodriguez et al 2009) is endowed with antimicrobial activity at high ionic concentrations, which is a crucial aspect due to the high-salt environment existing at the apical side of CF epithelial cells. In addition, in vivo experiments revealed that Esc(1-21) prolongs survival of murine models of P. aeruginosa-induced sepsis or lung infection, upon intravenous or intra-tracheal administration, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, expression profiling is considered as a fingerprint to find common and distinct responses that could aid in the design of combined therapies of unrelated compounds, to which AMP might contribute. However, this type of studies are still scarce in the case of AMP, with only a few examples in bacteria [26-29] and fungi, mostly yeast [30-33]. Transcriptome profiling has been used to characterize the response of the model yeast Saccharomyces cerevisiae to distinct antifungals [34-39], including selected AMP [30,33].…”
Section: Introductionmentioning
confidence: 99%